2021
DOI: 10.1186/s41983-020-00254-4
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation as a prophylactic treatment in migraine

Abstract: Background Clinical applications of transcranial magnetic stimulation (TMS) have shown promising results in the treatment of headache disorders, with migraine being one of the most encountered. Objective To assess the role of low-frequency repetitive transcranial magnetic stimulation as a preventive treatment of migraine (with and without aura) and correlate the results with the serum level of the inflammatory biomarker (neurokinin A). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A meta-analysis shows effectiveness of TMS in treating migraine with aura [34]. Prophylactic inhibitory rTMS at vertex in patients with known migraine regardless of the presence of aura apparently also reduces migraine median frequency by 12 days per month and median intensity by 6 points [35].…”
Section: Migraine With Auramentioning
confidence: 99%
“…A meta-analysis shows effectiveness of TMS in treating migraine with aura [34]. Prophylactic inhibitory rTMS at vertex in patients with known migraine regardless of the presence of aura apparently also reduces migraine median frequency by 12 days per month and median intensity by 6 points [35].…”
Section: Migraine With Auramentioning
confidence: 99%
“…Magnetic signals can penetrate the skull and stimulate the brain nerves without attenuation [4] . Azza et al purposefully evaluated the preventive therapeutic effects of low-frequency repetitive transcranial magnetic stimulation (rTMS) on migraine (with and without aura) and its correlation with the level of serum inflammatory biomarkers (neurokinin A) [5] . The study found that the pain intensity, attack frequency, attack duration and migraine disability score of patients with migraine were significantly reduced after transcranial magnetic stimulation treatment, and the patient's serum neurokinin A level was also significantly reduced.…”
Section: Clinical Study Of Transcranial Magnetic Stimulation For Migrainementioning
confidence: 99%